Impact Of Financial Capability On Sustainable Growth Of Listed Businesses In Vietnam (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to analyze the impact of financial capability on the sustainable growth of listed businesses in Vietnam. The research sample consists of 68 listed companies, corresponding to 628 observations during the period from 2010 to 2022. By using qualitative research methods (synthesis method; interpretative method) and quantitative research methods (linear regression method), the author identified six financial capability factors that influence sustainable growth: (1) Firm size (Size); (2) Short-term debt ratio (Std); (3) Fixed asset investment ratio (Inv); (4) Return on assets (ROA); (5) Return on equity (ROE); (6) Age of the company (Age). Based on the research findings, the author provides discussions and evaluations on the crucial role of enhancing financial capability of businesses, along with financial solution recommendations to achieve sustainable growth for listed businesses in Vietnam amidst the Industry 4.0 revolution.